PROJECTION ANALYSIS OF STATES GROSS DOMESTIC PRODUCT USING DISCRETE DYNAMICAL SYSTEMS - Rahela Abdul Rahim; Faezzah Mohd Daud; Noraziah Man; Fatinah Zainon (Journal of Islamic, Social, Economics and Development, 2019)
Gross Domestic Product (GDP) represents the total monetary value of all goods and services produced over a specific time period. This study models the GDP data of the state of Melaka and Negeri Sembilan for year 2005-2016. A mathematical model is developed for the state GDP data using Discrete Dynamical system model. The long-term equilibrium value for GDP were estimated using different parameter values. The future GDP for the states were also predicted using the suitable parameter value